Woman Critiqued Translated Essays on Japanese Women's Writing - Aoyama, Tomoko; Bardsley, Jan; Copeland, Rebecca L; Copeland, Rebecca L.; Copeland, Rebecca L.; Ericson, Joan E.; Hartley, Barbara; Seaman, Amanda (University of Hawaii Press, 2006)
"Woman Critiqued will make us wonder why we thought we could grasp modern Japanese literature without concerted attention to what men and women had to say about women's literary production. This remarkable collection is full of surprises, even where predictable arguments are being made. Careful translations of writings by the familiar and the obscure, together with thought-provoking introductions and supporting apparatus, make this an indispensable text for the study of modern Japanese culture and society." -Norma M. Field, University of ChicagoOver the past thirty years translations of Japanese women's writing and biographies of women writers have enriched and expanded our understanding of modern Japanese literature.